2018
DOI: 10.1002/cbf.3329
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ZAKβ in human osteosarcoma cells enhances ZAKα expression, resulting in a synergistic apoptotic effect

Abstract: ZAK is a mixed lineage kinase involved in cell differentiation, proliferation, and hypertrophic growth. ZAKα isoform of ZAK is associated with tumorigenesis, but the function of ZAKβ is not yet known. In H9c2 cells, ZAKβ was found to ameliorate the apoptotic effect induced by ZAKα. However, in osteosarcoma cells, ZAKβ elevates the apoptotic effect induced by ZAKα. In this study, we show that similar to ZAKα, the ZAKβ induces apoptosis and decreases cell viability. Interestingly, the expression of ZAKβ is depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…ZAKβ can also activate JNK in response to saturated free fatty acids (FFA) [15]. In human OS cells, we found that ZAKβ could enhance ZAKα expression, resulting in a synergistic apoptotic effect [5,16]. In this study, we demonstrate that 3-HF can induce ZAK overexpression to trigger human OS cells apoptosis, and ZAKβ can play a leading role in activating ZAKα and a synergistic apoptotic effect.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…ZAKβ can also activate JNK in response to saturated free fatty acids (FFA) [15]. In human OS cells, we found that ZAKβ could enhance ZAKα expression, resulting in a synergistic apoptotic effect [5,16]. In this study, we demonstrate that 3-HF can induce ZAK overexpression to trigger human OS cells apoptosis, and ZAKβ can play a leading role in activating ZAKα and a synergistic apoptotic effect.…”
Section: Introductionmentioning
confidence: 64%
“…In our previous publication, we demonstrated that doxorubicin can induce cell apoptosis by overexpression of ZAK in human OS cells [5]. Furthermore, we have also demonstrated that ZAKβ can enhance ZAKα expression in human OS cells, resulting in a synergistic apoptotic effect [16]. However, due to the adverse side effects associated with doxorubicin, various alternative drugs are under consideration [25,26].…”
Section: Discussionmentioning
confidence: 99%